A New Assay for Copper(II) Sulfate by Acidometry and Its Comparison with Iodometric Assay - Mir, S.A.; Shakoor, A. (Asian Journal of Chemistry, 2010)
An acidimetric assay for copper(II) sulfate has been developed and compared with iodometric assay. The assay is based on complete precipitanon of copper(II) as cupric hydroxide in presence of dilute sodium hydroxide solution; reconstituting the purified precipitate in slight excess of standard H2SO4, determining the amount of cupric hydroxide by backtitration of the solution against standard sodium hydroxide solution, wherein copper(II) ions act as self-indicator, and the end-point is characterized by appearance of a faint bluish-white turbidity that does not disappear on shaking and standing. Each mL of 1N H2SO4 consumed is equivalent to 1mL of 1N Cu(OH)2 that is equivalent to 31.77 mg of copper(II), or 124.85 mg of copper(II) sulfate pentahydrate. The assay is comparable to iodometric assay with no significant difference between mean percent purity values (P> 0.1), and precisions of two sets of data (P> 0.1). Acidimetric assay offers certain advantages over iodometric assay. It is simpler to perform, obviates the use of external indicator, and involves lesser number of chemicals and variables. The technique can be employed for determining percent purity of commercially produced copper (II) sulfate or other copper salts following their conversion to copper sulfate.